Cultivated forage production in the mid and high altitude areas of Ethiopia - Assefa, Getnet; Bezabih, Melkamu; Mekonnen, Kindu; Adie, Aberra; Gebreyes, Million; Seifu, Haimanot (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Feed is the main constraint of livestock production in Ethiopia. The major feed resources are inadequate and poor in quality. Grazing lands are shrinking and degraded, and crop residues are very poor in quality. The formulated concentrate feeds and agro-industrial by products are highly inflated in price, and not affordable to most smallholder livestock producers. Under such scenarios transformation of livestock productivity in Ethiopia needs to bring a breakthrough in quality feed production and supply. Cultivated forage crops are the feasible options to increase feed availability and quality, to protect the environment and much more. This brief describes the potential of cultivated forage crops and the basic production practices for selected and recommended forage crops in mixed crop–livestock production systems in Ethiopia